An optimization of role of a head nurses to hand hygiene compliance of nurses in outpatient clinic room - Gorean, Grace Irma; Novieastari, Enie; Wildani, Andi Amalia; Wigiarti, Sri Herni (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The culture of infection prevention and control, including hand hygiene is often not implemented properly by nurses in health services in outpatient units throughout the world. One of the factors related to nurses' compliance behavior in carrying out hand hygiene at inappropriate moments is the quality and quantity of the direction function of the head of the room as the first line manager. Purpose: To optimize the direction function of the head of the room regarding the implementation of nurse hand hygiene compliance in the outpatient room. Method: A descriptive approach, specifically focusing on case report study. The study took place from September-Oktober 2024, in Hospital X, Jakarta. The independent variable was direction function of head nurse the dependent variables is nurses hand hygiene compliance. Using total sampling, 14 respondent were selected, who met specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of quistioannare characteristics. Results: The evaluation and optimization by the direction function of the head of the room using the WHO multimodal approach, supervision from 69.2% to 90%, motivation from 69.2% to 90%, effective communication from 76.9% to 90%. Conclusion: The implementation of the directing function by the head of the room using the WHO multimodal approach has succeeded in improving the hand hygiene compliance of nurses in the pediatric outpatient room at X Hospital. This is evidenced by the results of the questionnaire survey which showed a significant increase.